The Exit Strategy Clause as an Application of the Proportionality Principle in Franchise Agreements - Nur Aini Musyafa'ah; Hardian Iskandar (Jurnal Daulat Hukum, 2025)
This study aims to analyze the application of the proportionality principle in formulating exit strategy clauses in franchise agreements and examine legal protections available to franchisees facing unilateral termination without proportional clauses. This study employs a normative legal approach examining legislation, academic literature, and franchise practices through conceptual, legislative, and case approaches. The novelty of this research lies in applying the proportionality principle specifically to exit strategy mechanisms, an aspect rarely explored in Indonesian franchise law literature, offering practical frameworks for balanced contract termination. The proportionality principle applies through three tests (suitability, necessity, and balancing). A proportional exit strategy clause must contain a clear termination mechanism with a cure period, fair compensation based on franchisee investment and contribution, and an adequate transition period for business cessation. Legal protection for franchisees includes preventive measures through notarial agreements and repressive measures through legal remedies based on the Civil Code, compensation claims, buyback mechanisms, protection during franchisor bankruptcy, and proportional non-competition clauses. This study emphasizes that applying proportionality principles in exit strategy clauses is crucial for ensuring balance between parties rights and obligations and preventing contractual power abuse.